2007
DOI: 10.1111/j.1445-6664.2007.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two surfactant series on the absorption and translocation of 14C‐glyphosate in sicklepod and prickly sida

Abstract: The weed species, prickly sida (Sida spinosa L.) and sicklepod (Senna obtusifolia L.), were treated with 14 C-glyphosate alone and formulated with different polyethlylane oxide (PEO) surfactants in tallow amine ethoxylate and non-ionic alkoxylate series to determine the amount of 14 C-glyphosate absorption and translocation. The surface tension, contact angle, and 14 Cglyphosate distribution were significantly affected by both the presence of different waxes on the plants and by the addition of surfactants to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…The radiolabeled treatment was mixed with a glyphosate product that contained an adjuvant, but different adjuvants could increase foliar uptake levels of JS-501 (Sharma and Singh, 2007). The radiolabeled treatment was mixed with a glyphosate product that contained an adjuvant, but different adjuvants could increase foliar uptake levels of JS-501 (Sharma and Singh, 2007).…”
Section: Shikimate Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The radiolabeled treatment was mixed with a glyphosate product that contained an adjuvant, but different adjuvants could increase foliar uptake levels of JS-501 (Sharma and Singh, 2007). The radiolabeled treatment was mixed with a glyphosate product that contained an adjuvant, but different adjuvants could increase foliar uptake levels of JS-501 (Sharma and Singh, 2007).…”
Section: Shikimate Assaymentioning
confidence: 99%
“…cultivars. The radiolabeled treatment was mixed with a glyphosate product that contained an adjuvant, but different adjuvants could increase foliar uptake levels of JS-501 (Sharma and Singh, 2007). Perhaps, perennial ryegrass has enhanced absorption of glyphosate applied with other adjuvants or formulations and warrants further investigation.…”
Section: Shikimate Assaymentioning
confidence: 99%
“…Sharma and Singh determined that the absorption and translocation of 14 C-glyphosate, surface tension, contact angle, and distribution of 14 C-glyphosate were significantly affected by the presence of different waxes and the addition of glyphosate surfactant. The results showed that the contact angle values of glyphosate-added and nonglyphosate-added surfactants increased significantly with the increase in PEOs.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, in order to effectively absorb the active ingredients in pesticide formulations and reduce the use of pesticides, studies have investigated the changes of 12 nonionic surfactant micelles in the process of pesticide solubilization, 12 which holds that pesticide solubilization will lead to lower cloud points, micelle stretching, micelle shape transformation, and dehydration of surfactant head groups, and further solubilization will make surfactant micelles rehydrate. 13 Sharma and Singh 14 determined that the absorption and translocation of 14 C-glyphosate, surface tension, contact angle, and distribution of 14 C-glyphosate were significantly affected by the presence of different waxes and the addition of glyphosate surfactant. The results showed that the contact angle values of glyphosate-added and nonglyphosate-added surfactants increased significantly with the increase in PEOs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Segundo , a falta de metabolismo de glyphosate em AMPA pode acontecer devido ao alto grau de toxicidade do tratamento glyphosate, fato comprovado por Cessna et al (2002) BAYLIS, 2000;CESSNA et al, 2002;SHARMA;SINGH, 2007 Controle 0,00 (±0,00) NS 0,00 (±0,00) c 0,00 (±0,00) NS 0,01 (±0,01) NS 0,00 (±0,00) NS 0,02 (±0,00) c 0,00 (±0,00) NS 0,00 (±0,01) NS Rodeo 0,00 (±0,00) NS 0,01 (±0,01) c 0,00 (±0,00) NS 0,01 (±0,01) NS 0,00 (±0,00) NS 0,06 (±0,08) bc 0,01 (±0,01) NS 0,01 (±0,02) NS R. Original 0,01 (±0,01) NS 0,28 (±0,04) a 0,01 (±0,01) NS 0,00 (±0,01) NS 0,01 (±0,01) NS 0,18 (±0,02) a 0,00 (±0,00) NS 0,01 (±0,01) NS R. Ready 0,00 (±0,00) NS 0,20 (±0,01) b 0,00 (±0,00) NS 0,01 (±0,01) NS 0,03 (±0,02) NS 0,16 (±0,05) ab 0,03 (±0,02) NS 0,01 (±0,01) NS Há necessidades de pesquisas para testar a hipótese de absorção de AMPA pelas raízes de plantas das parcelas controle após a aplicação de AMPA diretamente no solo em parcelas adjacentes.…”
Section: Piracicaba 2007/2008unclassified